2020
DOI: 10.1002/cre2.286
|View full text |Cite
|
Sign up to set email alerts
|

A nonsurgical treatment of peri‐implantitis using mechanic, antiseptic and anti‐inflammatory treatment: 1 year follow‐up

Abstract: Aims The study's aim was to assess the clinical outcome 6 and 12 months after a nonsurgical treatment of peri‐implantitis per se or in conjunction with a combination of local antiseptic and anti‐inflammatory treatment. Materials and methods Included were 69 patients with periodontitis, with 106 implants, diagnosed with peri‐implantitis. Peri‐implantitis was defined as radiographic bone loss ≥3 mm, probing depth (PD) ≥ 6 mm, with bleeding on probing. Group M peri‐implantitis was treated with ultrasonic debridem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Under peri-implantitis, now we recognize plaque-associated pathological condition of peri-implant tissues, characterized by inflammatory process of mucosa and progressive bone loss near the dental implants, and can be defined by the identification of several signs such as bleeding or suppuration during careful probing and progressive of peri-implant bone loss beyond the crestal ridge due to initial bone remodeling. In the absence of all these signs, the diagnosis can be provided according the combination of the following criteria: depth of probing not less than 6 mm, appearance of bleeding or suppuration during this measurement test, and the bone loss level with apical direction not less than 3 mm in comparison to coronal intraosseous part of dental implant [6][7][8]. Now, the prevalence of peri-implantitis is higher than it was considered before: during the first 10 years after dental implantation, it varies from 1% to 47% according to a systematic review of Derks and Tomasi (2015) and even about 85% in the work of Dreyer (2018) [9,10], especially in conditions of comorbidity, poor oral hygiene, and bad habits like smoking.…”
Section: Introductionmentioning
confidence: 99%
“…Under peri-implantitis, now we recognize plaque-associated pathological condition of peri-implant tissues, characterized by inflammatory process of mucosa and progressive bone loss near the dental implants, and can be defined by the identification of several signs such as bleeding or suppuration during careful probing and progressive of peri-implant bone loss beyond the crestal ridge due to initial bone remodeling. In the absence of all these signs, the diagnosis can be provided according the combination of the following criteria: depth of probing not less than 6 mm, appearance of bleeding or suppuration during this measurement test, and the bone loss level with apical direction not less than 3 mm in comparison to coronal intraosseous part of dental implant [6][7][8]. Now, the prevalence of peri-implantitis is higher than it was considered before: during the first 10 years after dental implantation, it varies from 1% to 47% according to a systematic review of Derks and Tomasi (2015) and even about 85% in the work of Dreyer (2018) [9,10], especially in conditions of comorbidity, poor oral hygiene, and bad habits like smoking.…”
Section: Introductionmentioning
confidence: 99%
“…242 More effectively, adjunctive approaches where antibiotics or antibacterial agents, such as chlorhexidine, are employed in addition to the debridement methods. 243,244 Surgical therapy for peri-implantitis can be done through various techniques such as simple access flaps for cleaning, apically repositioned flap and access flap and bone recontouring or regenerative procedures with plaque control. 238,245 When a complete biofilm removal is not possible with one treatment, then a combination of treatments may be performed.…”
Section: Existing and Emerging Strategies Against Peri-implantitismentioning
confidence: 99%
“…However, these mechanical debridement methods have failed to affect pocket depths and reduce bacterial counts in peri-implantitis. , Laser (or photodynamic) and air-abrasive devices have also been used; however long-term effects of these nonsurgical methods remain uncertain . More effectively, adjunctive approaches where antibiotics or antibacterial agents, such as chlorhexidine, are employed in addition to the debridement methods. , Surgical therapy for peri-implantitis can be done through various techniques such as simple access flaps for cleaning, apically repositioned flap and access flap and bone recontouring or regenerative procedures with plaque control. , When a complete biofilm removal is not possible with one treatment, then a combination of treatments may be performed . In general, the strategy is to dilute (the inoculum size), disrupt (the biofilm) and detoxify (the implant).…”
Section: Existing and Emerging Strategies Against Peri-implantitismentioning
confidence: 99%
“…19 Recently, some studies have shown that macrophage phenotype and specific interleukins may play an important role in disease pathogenesis and progression of peri-implantitis [38][39][40] and, therefore, future trends to treat peri-implantitis may involve antiinflammatory agents to modulate inflammation and counteract peri-implant tissue destruction. [41][42][43]…”
Section: Treatment Of Peri-implantitismentioning
confidence: 99%